Towards a green economy : pathways to sustainable development and poverty eradication. - UNEP; United Nations Environment Programme ([Nairobi, Kenya] : UNEP, 2011)
The report is compiled by UNEP's Green Economy Initiative in collaboration with economists and experts worldwide. It demonstrates that the greening of economies is not generally a drag on growth but rather a new engine of growth; that it is a net generator of decent jobs, and that it is also a vital strategy for the elimination of persistent poverty. The report also seeks to motivate policy makers to create the enabling conditions for increased investments in a transition to a green economy.
Machine generated contents note: pt. I Investing in natural capital -- Agriculture -- Fisheries -- Water -- Forests -- pt. II Investing in energy and resource efficiency -- Renewable energy -- Manufacturing -- Waste -- Buildings -- Transport -- Tourism -- Cities -- pt. III Supporting the transition to a global green economy -- Modelling global green investment scenarios -- Enabling conditions -- Financing.
Includes bibliographical references.
Keywords: Economic development -- Environmental aspects; Environmental economics; Green movement; Sustainable development; Poverty